2014
DOI: 10.1016/j.jebo.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in risk aversion: Do single-sex environments affect their development?

Abstract: Gender Differences in Risk Aversion: Do Single-Sex Environments Affect their Development? * Single-sex classes within coeducational environments are likely to modify students' risktaking attitudes in economically important ways. To test this, we designed a controlled experiment using first year college students who made choices over real-stakes lotteries at two distinct dates. Students were randomly assigned to classes of three types: all female, all male, and coeducational. They were not allowed to change gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 29 publications
6
69
1
2
Order By: Relevance
“…Although many personality traits may in part be biologically determined, for example differences in testosterone levels and risk aversion in Maestripieri et al (2009) Booth and Nolen (2012a, b) and Booth et al (2014) find that girls from single-sex schools behave more like boys in terms of risk attitudes and willingness to compete. The authors speculate that girls may reinforce stereotypical behaviour to appear attractive when boys are present, while boys may exhibit assertiveness to attract the opposite sex and reduce threats from competitors.…”
Section: Gender Gaps In Field Preferences and Intergenerational Transmentioning
confidence: 99%
“…Although many personality traits may in part be biologically determined, for example differences in testosterone levels and risk aversion in Maestripieri et al (2009) Booth and Nolen (2012a, b) and Booth et al (2014) find that girls from single-sex schools behave more like boys in terms of risk attitudes and willingness to compete. The authors speculate that girls may reinforce stereotypical behaviour to appear attractive when boys are present, while boys may exhibit assertiveness to attract the opposite sex and reduce threats from competitors.…”
Section: Gender Gaps In Field Preferences and Intergenerational Transmentioning
confidence: 99%
“…The Big Five personality traits were constructed following Heineck (2007). See Booth, Cardona Sosa and Nolen (2011) for further details.. 5 See row 6 in Table 1; men are more likely to pick option A in Q2 after choosing option B in Q1.…”
Section: Resultsmentioning
confidence: 99%
“…This gender difference between the tribes suggests the importance of socially defined gender roles in shaping attitudes toward competition. Similarly, a series of studies by Alison Booth and her co-authors revealed that single-sex schools or classrooms nurture more competitive attitudes and encourage risk-taking behavior in women (Booth et al, 2014;Nolen, 2012a, 2012b;Booth et al, 2011). 8 There is also evidence that suggests that having same-sex instructors in introductory math or science courses encourages women to major in math or engineering (Carrell et al, 2010), indicating that having a same-sex role model is an environmental factor that could induce women to make choices that they otherwise would not.…”
Section: Introductionmentioning
confidence: 99%